C-MYC and BCL2 translocation frequency in diffuse large B-cell lymphomas: A study of 97 patients - Bahar Akkaya; Ozan Salim; Hampar Akkaya; Mualla Ozcan; Orhan Kemal Yucel; Ramazan Erdem; Utku Iltar; Levent Undar (Wolters Kluwer Medknow Publications, 2016)
Purpose: Diffuse large B-cell lymphoma (DLBCL) is an aggressive non-Hodgkin lymphoma with marked biologic heterogeneity. MYC and BCL2 rearrangements have been reported in a proportion of DLBCLs, where they may be associated with an adverse clinical outcome. The aim of this study was to determine the frequency of MYC and BCL2 translocations in DLBCL and assess the prognostic impact in DLBCL patients. Materials and Methods:   In the present study, we evaluated the expression patterns of CD 10, BCL6, and MUM 1 by immunohistochemistry in 121 cases with DLBCL in tissue microarray (TMA): 62 cases in germinal center B-cells (GCBs); and 59 cases in activated B-cells (ABCs) of which 60 were females and 61 were males. MYC and BCL2 rearrangements were investigated by interphase fluorescence in situ hybridization on TMAs in 97 DLBCLs. Result: MYC rearrangements were observed in 11 of 97 cases. There was no association with other clinical features, including age, sex, and nodal/extranodal disease. MYC rearrangement was associated with significantly worse overall survival (P < 0.01). BCL2 rearrangements were observed in 14 of 97 cases. There was no association with other clinical features including age and sex. BCL2 rearrangement had a worse outcome (P < 0.01). MYC and BCL2 rearrangements were observed in 3 of 97 cases with the age of  53 (female), 53, 63 years old, respectively, died in 24, 18, and 35 months after the diagnosis. Two cases had primary nodal and one case primary extranodal presentations. All these patients had stage IV disease. Conclusion: We concluded that C-MYC and BCL2 may contribute to aggressive transformation, and more mechanism-based therapy should be explored. Targeted therapies involving these rearrangements and its associated pathways may change the fate of DLBCLs. Analysis of MYC gene rearrangement along with BCL2 is critical in the identification of high-risk patients with poor prognosis.